Levofloxacin or gonadotropin releasing hormone agonist treatment decreases intrauterine microbial colonization in human endometriosis. (September 2021) - Khan, Khaleque N; Fujishita, Akira; Muto, Hideki; Masumoto, Hiroshi; Ogawa, Kanae; Koshiba, Akemi; Mori, Taisuke; Itoh, Kyoko; Teramukai, Satoshi; Matsuda, Katsuya; Nakashima, Masahiro; Kitawaki, Jo
Highlights: Using 16S rDNA metagenome assay and immunohistochemical analysis, we found that treatment with levofloxacin and/or GnRHa decreases uterine infection with consequent decrease in the occurrence of tissue inflammation, cell proliferation, and angiogenesis in endometria of women with endometriosis. This new treatment strategy in women with endometriosis was associated with substantial decrease in the occurrence of chronic endometritis. These findings were coincided with significantly decreased tissue inflammation, cell proliferation and angiogenesis in endometriotic lesions with histology proven improvement in the morphological appearance of ovarian endometrioma. Abstract: Objective: We examined the hypothesis that antibiotic treatment with or without gonadotropin releasing hormone agonist (GnRHa) may decrease intrauterine infection with consequent decrease in tissue inflammation, cell proliferation and angiogenesis in human endometriosis. Study design: This is a prospective non-randomized observational study. Endometrial/endometriotic samples were collected during surgery from 53 women with endometriosis and 47 control women who were treated with levofloxacin (LVFX, 500 mg, once per os) or GnRHa (1.88 mg/IM for 3 months) before surgery. Endometrial samples were analyzed by broad-range polymerase-chain reaction (PCR) amplification of bacteria targeting V5-V6 region of 16S rRNA gene. Immunohistochemical analysis was performed using antibodies against CD138 (Syndecan-1, a marker of plasma cells), CD68 (marker of macrophages), Ki-67 (cell proliferation marker), and CD31 (vascular cells marker). Results: 16S rDNA metagenome assay indicated that treatment with either of LVFX or GnRHa + LVFX significantly decreased some components of major bacterial genera comparing to untreated group. In women with endometriosis, treatment with either of LVFX or GnRHa + LVFX significantly decreased Gardnerella, Prevotella, Acidibactor, Atopobium, Megasphaera, and Bradyrhizobium (p < 0.05 for each) comparing to untreated group. Cochran-Mantel-Haenszel test indicated that occurrence rate of chronic endometritis was significantly decreased after GnRHa + LVFX treatment comparing to GnRHa treatment group (p = 0.041). These findings were coincided with significantly decreased CD68-stained macrophage infiltration, Ki-67- stained cell proliferation and CD31-stained micro-vessel density in endometria and endometriotic lesions with histology proven improvement in the morphological appearance of ovarian endometrioma. Conclusions: These findings suggest that clinical administration of a broad-spectrum antibiotic with or without GnRHa may be effective in improving uterine infection with decrease of tissue inflammation, cell proliferation, and angiogenesis in human endometriosis.